Reform of the UN development system: new multilateralist reform coalition needed - Silke Weinlich (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
The United Nations (UN) development system is well established and ubiquitous in the global development system. Its functions range from providing a forum for dialogue, decision- making and norm-setting, to research, advocacy, technical assistance and humanitarian aid. The UN's universality and neutrality, its broad mandate, and its embodiment of a rulebased international system are assets that the world will need even more in times of multiple global crises. However, the UN development system is in need of thorough reform. It currently punches below its weight. What reform options are on the table? Reform options include the radical merger of agencies, or the more incremental building of a unified country presence (Delivering as One Initiative). Some argue that the UN should gain clout visà-vis the Bretton Woods Institutions. Others argue that it should confine itself to niche areas (such as fragile countries)where it can perform better than other actors considered less legitimate and neutral. How do key stakeholders position themselves? Negotiations remain mostly trapped in the traditional North-South conflict in spite of evidence that the divide no longer reflects global power structures. Western donors push for a rationalised UN with greater focus, efficiency, and development effectiveness. Developing countries perceive this as an attempt to further marginalize the UN in questions of economic development. Current reform dynamics The most recent round of reform negotiations showed that the time is not yet ripe for a consensus on fundamental reforms. But more incremental reforms gained approval and have led to improvements. UN agencies are becoming more results-oriented, working more closely together and harmonising their business practices. The Delivering as One pilot initiative shows promise. What lies ahead? Incremental reforms have their merits. There is real room for improvement if governments act more coherently across governing bodies and make UN agencies deliver better results more efficiently. But there are limits to what can be achieved. Governments should begin to strategically build the basis for a more fundamental reform of the UN and its development system. New multilateralist reform coalition Political leadership is necessary to overcome the North-South divide at the UN. A new multilateralist reform coalition is called for. The Global Governance Group, initially formed to demand a more inclusive G-20 process, might become its nucleus. But not only small states should rediscover the merits of the UN which – however imperfect – stands for an international system based on the rule of law. The key to success or failure will be the attitude of emerging powers in the UN. Currently the potential of the UN and its development system is hardly tapped. Governments should prepare to change that.
Keywords: 330